Gut transit rate in Atlantic salmon ( Salmo salar ) exposed to optimal and suboptimally high water temperatures - Tom Mock; Zakarya HRAA Alkhabbaz; Melissa M Rocker; Michael J Lewis; Erin E Cumming; Richard P Smullen; Giovanni M Turchini; David Francis (2022)
Gut transit rate in Atlantic salmon ( Salmo salar ) exposed to optimal and suboptimally high water temperatures